THE CONSTRUCTION OF THE MAIN MALE CHARACTER'S MASCULINITY IN TWO VERSIONS OF LITTLE WOMEN - Syahla Jilan Safitri, - (2021)
The practice of adaptation has become commonplace in literary works, including the film industry. One of the most widely adapted works is the Little Women novel which has been adapted into at least six films from 1917 to 2019. The number of adaptations makes the audience see different versions of the same character. This study aims to investigate the construction of Laurie as the main male character in two versions of Little Women films directed by women, which are Little Women (Armstrong, 1994) and Little Women (Gerwig, 2019). Using a qualitative-descriptive approach, this study employs Boggs and Petrie's (2012) theory of characterization, masculinity theory by Connell (2005), and some of the cinematic aspects (i.e., mise-en-scene and camera works) proposed by Bordwell and Thompson (2008). The findings of this study reveal that Laurie's character in both versions has the fluidity of masculinity, in which Laurie's character is able to change his masculinity within the same film from hegemonic to complicit depending on the situation in the films, especially when Jo's character is around him. Moreover, Laurie in the former version is portrayed to be more complicit while Laurie in the latter version shows the hegemonic traits more often.